AN EMPIRICAL STUDY TO ANALYSE CUSTOMER BEHAVIOUR FOR BUYING ELECTRIC VEHICLES - Satish, Monangi; Kovuri, Uday; Goud, Rahul Kumar; Khatua, Dr. Subhadarshini (The journal of contemporary issues in business and government, 2023)
The production and distribution of electric cars are gaining momentum as a direct result of contemporary environmental concerns. The year 2018 has fundamentally altered the way in which Indian manufacturers think about electric vehicles as superior replacements for gasoline-powered automobiles. The purpose of this thesis is to explore the variables impacting the commercial success of electric vehicles in India as well as the intention of consumers to acquire such vehicles. There are several aspects of the scenario, such as the regulatory environment, as well as personal and current psychological elements, such as attitude and perception, as well as societal acceptability and consideration levels, which all play a role in the choice of prospective automobile purchasers. The present body of literature on the subject of electric automobiles in the Indian setting will be the focus of this study, and its primary objective will be to provide new information in the area. This study will employ mixed methods to understand the customer buying intention towards electric vehicles. We will conduct the quantitative method first followed by the quantitative study. The quantitative study will help uncover the insights which we could have missed in the quantitative work. The data will be collected via the use of surveys that will be carried out with the aid of Google Forms, and then it will be analysed using an appropriate statistical test. The results of the study will enable us to comprehend the current scenario of customer buying intentions towards EVs in India and draw a conclusion based on it.